Problems in realizing study models on mathematics - Novikienė, Regina; Čiučiulkienė, Nijolė (Lietuvos matematikos rinkinys, 2023)
The reflective study models are quite frequent and well analyzed in the scientific literature. Still their realization premises being different in many countries keep forming a scientific issue which needs a special attention, especially in learning mathematics. In this context there arises a problem question: what are the realization limitations of the traditional and reflective mathematics learning models? The research paper consists of two parts. The first part clears a problems of the realization a traditional study model. The second part clears out the possible realization limitations of the above mentioned model in Lithuanian context.